A Green and Scalable Synthesis of Na3Fe2(PO4)P2O7/rGO Cathode for High‐Rate and Long‐Life Sodium‐Ion Batteries. Issue 8 (25th June 2021) - Wang, Huiming; Pan, Zibing; Zhang, Haotian; Dong, Chongrui; Ding, Yan; Cao, Yuliang; Chen, Zhongxue
Abstract: Sodium‐ion battery has been considered as one of the most promising power sources for large‐scale energy storage systems due to its similar electrochemistry to the lithium‐ion battery and the crust abundance of Na resources. Essentially, developing low‐cost electrode materials along with a facile and economical synthesis procedure is critically important to promote the commercialization of sodium‐ion batteries. However, applicable cathode materials capable of being massively produced are still scarcely reported to date. Herein, a green and scalable synthesis approach is developed to obtain Na3 Fe2 (PO4 )P2 O7 (NFPP)/rGO composite by using FePO4 and Na3 PO4 as the resources, during which all the atoms present in the starting materials end up in the product. The prepared Na3 Fe2 (PO4 )P2 O7 /rGO cathode exhibits an ultralong cycle life (capacity retention of 72.4% after 8000 cycles at 20 C) and outstanding rate capability (42.4 mAh g −1 at 100 C). In particular, the NFPP/rGO‐HC full battery assembled by the Na3 Fe2 (PO4 )P2 O7 /rGO cathode and hard carbon anode demonstrates an energy density of 192 Wh kg −1 and superior cycling performance (capacity retention of 85.2% after 500 cycles). These results will contribute to the development of sodium‐ion batteries from applicable Na3 Fe2 (PO4 )P2 O7 /rGO cathode material. Abstract : A green and atom economical synthesis procedure is developed to massively produce Na3 Fe2 (PO4 )P2 O7 /rGO composite by using FePO4 and Na3 PO4 as the resources. The obtained cathode demonstrates long‐term cycle life, high rate capability, and an energy density of 192 Wh kg −1 in both half‐cell and full battery coupling with a hard carbon anode.